(untitled) (Alternautas, 2016)
The whole extensive historical formational process of the Global Coloniality of Power has entered a deep crisis. The “Bien Vivir”, an expression of the indigenous populations of Latin America, is shaping an alternative for social life that can only be realized as a De/Coloniality of Power.